Toward a race-conscious pedagogy in legal education - Crenshaw, Kimberle Williams (National Black Law Journal, 1988)
Keywords: afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; féminismes noirs; ressource en ligne; régions géographiques; science politique et droit; états-unis

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis